Overview: Structural change, fundamentals, and growth - McMillan, Margaret S.; Rodrik, Dani; Sepúlveda, Claudia (International Food Policy Research Institute, 2017)
The first decade of the 21st century was extraordinarily good for developing countries and their mostly poor citizens. Their economies expanded at unprecedented rates, resulting in both a large reduction in extreme poverty and a significant expansion of the middle class. In fact, their growth rates were an average 4 percentage points faster than those of the advanced countries—versus only 1.3 percentage points in the 1990s (Figure O.1a). This growth was led by the efforts of China, India, and a small number of other Asian countries, and assisted by the weaker economic performance of the rich countries. Latin America and Africa resumed growth as well, catching up with—and often surpassing—the growth rates they experienced during the 1950s and 1960s. As a result, the developing countries moved more quickly to close the income gap with the advanced countries (Figure O.1b), a process known as economic convergence. More recently, however, that process has slowed down—reflecting a narrowing of the advanced and developing country growth rate differentials since 2010—making it unlikely that poorer countries will be able to close the development gap with richer countries anytime soon.